2014
DOI: 10.1016/j.neuroimage.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy investigations of functionally defined language areas in schizophrenia patients with and without auditory hallucinations

Abstract: Background: Cerebral dysfunction occurring in mental disorders can show metabolic disturbances which are limited to circumscribed brain areas. Auditory hallucinations have been shown to be related to defined cortical areas linked to specific language functions. Here, we investigated if the study of metabolic changes in auditory hallucinations requires a functional rather than an anatomical definition of their location and size to allow a reliable investigation by magnetic resonance spectroscopy (MRS). Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…However, lower order sensory areas, such as the auditory cortices have simpler receptive fields with only serial processing capabilities (Homan et al, 2014; Rauschecker and Scott, 2009; Yamada and Wilber, 1990). Given the fact that the pathophysiology of psychiatric disorders is so complicated and these disorders may have different influences on different neural systems and circuits, investigating the primary sensory areas may provide an advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lower order sensory areas, such as the auditory cortices have simpler receptive fields with only serial processing capabilities (Homan et al, 2014; Rauschecker and Scott, 2009; Yamada and Wilber, 1990). Given the fact that the pathophysiology of psychiatric disorders is so complicated and these disorders may have different influences on different neural systems and circuits, investigating the primary sensory areas may provide an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…A 31 P MRS study reported correlation between the hallucination score of the Positive and Negative Syndrome Scale (PANSS) and phosphomonoesters and phosphodiesters (Nenadic et al, 2014). A recent 1 H MRS study comparing hallucinations in the STG reported that NAA/Cr ratio correlated with total and negative subscore of the PANSS in schizophrenia (Homan et al, 2014). Neuronal activation patterns for patients with auditory hallucinations were more prominent for the left hemisphere when compared to non-hallucinating patients as shown by functional neuroimaging studies with auditory tasks (Dierks et al, 1999; Shinn et al, 2013), which may indicate the relevance of the left auditory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory verbal hallucinations have been shown to be related to defined cortical areas linked to specific language functions. Homan et al investigated the metabolic changes in auditory hallucinations requiring a functional rather than an anatomical definition of speech production and found significant differences in Broca's and Wernicke's areas associated with voice hearing in patients with schizophrenia.…”
Section: Cognitive Neurobiological Modelsmentioning
confidence: 99%
“…In teasing out state vs. trait aspects, Kuhn found the state of experiencing AVHs related to brain regions that have been implicated in speech production, that is, Broca's area, whereas trait proneness to AVHs seems to be related to areas involved in auditory stimuli processing and speech perception, that is, auditory cortex . In terms of brain metabolism, magnetic resonance spectroscopy studies have shown some evidence of association between severity of AVHs and left temporal/Heschl gyrus metabolism .…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) were presented as potential and safe methods to relieve the hallucinatory burden in those, who did not respond to conventional approaches. The main study presented (Homan et al, 2014) demonstrated involvement of the language system in the generation of AVH. The superior temporal lobe, including primary auditory cortex and its connections, was identified as a region involved in the generation, modulation and therapy of AVH.…”
Section: Non-pharmacologic Treatmentmentioning
confidence: 88%